1992
DOI: 10.1111/j.1365-2621.1992.tb11302.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Caseinate and Skim Milk Gels Formed by Incubation with Microbial Transglutaminase

Abstract: Several suspensions and emulsions containing commercial sodium caseinate or skim milk were gelatinized by Ca*+-independent microbial transglutaminase treatment. The characteristics of the gels were largely affected by the enzyme concentrations employed. For caseinate gels generally the higher enzyme concentration gave steep decreases in breaking strength, strain and cohesiveness of the gels. The creep tests on emulsified gels prepared to two different enzyme concentrations showed that the gel made with a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 11 publications
0
39
0
1
Order By: Relevance
“…It was further suggested that this repulsive layer had to be neutralised (through acidification) before gelation became evident. In contrast, Nonaka et al [28] showed that skim milk suspensions could be turned into self-supporting gels by using appropriate concentrations of transglutaminase and that the breaking strength and hardness of the gels were remarkably enhanced by employing higher enzyme concentrations. However, these authors used 150 g protein·kg -1 (430 g solids·kg -1 ) in their suspensions giving closely packed casein micelles, which would undoubtedly have lead to greater opportunities for intermicellar cross-linking compared to the protein concentration (~33 g·kg -1 ) of unconcentrated milk.…”
Section: Introductionmentioning
confidence: 99%
“…It was further suggested that this repulsive layer had to be neutralised (through acidification) before gelation became evident. In contrast, Nonaka et al [28] showed that skim milk suspensions could be turned into self-supporting gels by using appropriate concentrations of transglutaminase and that the breaking strength and hardness of the gels were remarkably enhanced by employing higher enzyme concentrations. However, these authors used 150 g protein·kg -1 (430 g solids·kg -1 ) in their suspensions giving closely packed casein micelles, which would undoubtedly have lead to greater opportunities for intermicellar cross-linking compared to the protein concentration (~33 g·kg -1 ) of unconcentrated milk.…”
Section: Introductionmentioning
confidence: 99%
“…MTGase from Streptoverticillium sp. used for several food applications such as producing polymers of casein and soybean proteins and gelatinizing sodium caseinate and skim milk gels [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…TGase, derived from a microorganism, has been found and mass produced (Ando et al, 1989). Enzymological properties and various basic effects on physical properties of food proteins have been reported Nonaka et al, 1992;Nonaka et al, 1994;Nonaka et al, 1996).…”
mentioning
confidence: 99%
“…TGase, derived from a microorganism, has been found and mass produced (Ando et al, 1989). Enzymological properties and various basic effects on physical properties of food proteins have been reported Nonaka et al, 1992;Nonaka et al, 1994;Nonaka et al, 1996).The principal mechanism of gelation of soy protein isolate (abbreviated SPI) is due to the formation of disulfide bonds, reported by Wolf and Smith (1961), Circle et al (1964), Aoki and Sakurai (1969), Saio et al (1971) on heat-induced gel, and by Watanabe et al (1963), andHashizume et al (1974) on freezeinduced gel. On the other hand, as described in previous reports (Soeda, 1994a;1994b;1995a;Soeda & Baba, 1999), the gel (abbreviated Cold-gel) was obtained by keeping it in cold storage.…”
mentioning
confidence: 99%